L’utilisation de l’informatique comme outil de gestion dans les assurances I.A.R.D. - Pilon, André (Assurances)

(untitled) (HEC Montréal, 1981)
In his article, Mr. André Pilon outlines a number of the computer applications available to the insurance industry. His intention is not to go into detail, rather to demonstrate the various uses of this relatively new form of information processing. He mentions particularly the issue of individual policies, rate calculation and the collection of valuable data regarding losses.